(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Pollen morphology of 13 taxa belonging to 5 genera of the tribe Phyllodoceae (Ericaceae) was examined by means of light and scanning electron microscopy (LM and SEM, respectively), or SEM alone. In Phyllodoceae, 3-colpor(oid)ate, minute to medium, oblate pollen grains are united usually in tetrahedral tetrads. Pollen tetrads are generally characterized by the presence of viscin threads except Elliottia pyroliflora, Epigaea asiatica and Phyllodoce caerulea. The absence of viscin threads might indicate to a secondary loss, since these are present at least in some species within all the genera of Phyllodoceae. The pollen morphological data confirm the infra- and inter-generic relationships as identified by molecular phylogeny of Phyllodoceae and/or vice-versa. Although various palynological characters were found to be taxonomically important at different taxonomic levels, the apocolpial exine sculpture is emerged as one of the most important palynological features of systematic importance. The rugulate apocolpial exine with striate secondary sculpture and a reduced colpus might be apomorphic palynological character states for this tribe and Ericaceae as well. Hitherto, it is the first SEM study of Rhodothamnus pollen. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21351 Bangladesh J. Plant Taxon. 21(2): 129-137, 2014 (December)